CONSUMERS’ PERCEPTION TOWARDS E-WALLETS IN HARYANA USING PLS-SEM APPROACH - Jaideep; Nimbrain, Nitu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Electronic wallets refer to an electronic system that allows an individual to make financial transactions digitally without using cash. The present study conducted in Haryana State that provides the factors that form Consumers’ Perception towards E-Wallets Services. The study used Partial Least Square- Structural Equation Modeling using SmartPLS-4 software and collected the primary data through a structured questionnaire from 1000 respondents from six administrative divisions of Haryana covering all 22 districts with the help of convenient sampling method. Variables have been measured using 5-point Likert scale. The out of the study is a conceptual model of Consumers’ Perception towards E-Wallets Services in Haryana. Finding of the study suggests that consumers’ form a positive perception when they find an e-wallet service simple, reliable, secure and efficient which uplift their social status.